THE ROLE OF HALAL LOGISTICS IN THE DEVELOPMENT OF INDONESIA’S NATIONAL ECONOMY - Maulidiyah Maulidiyah; Hadi Peristiwo (Tazkiya, 2023)
The Qur'an and Hadith as sources of Muslim law have made it clear that halal products are very important to be used by Muslims in Indonesia, therefore halal nowadays, many Indonesian people are interested in using it so halal products in Indonesia have become a sector that contributes greatly to the Indonesian economy. In addition to providing halal products that are good for those who consume them, they also provide economic value to the people in Indonesia who have a halal product business. Halal does not only concern product content but also relates to the halal logistics system and the halal supply chain. Literature study is used as a research method to gather insights from various national and international sources. Method collection data through secondary data obtained from various scientific works such as journals, articles, e-books, and the internet. Based on the results of the study, halal logistics is a logistics system based on segregation between halal and non-halal products. The purpose of separating halal and non-halal products is to avoid contamination of goods, avoid errors in handling goods, and ensure the consistency of halal handling as expected by Muslims. In addition to product halalness, the development of halal logistics also includes policies, infrastructure, facilities, and institutions. In addition, competency in human resources is also required in each process and information technology for monitoring the halal product flow.